Think. - Faure Walker, Caryn (Helsinki : UIAH (University of Art and Design Helsinki), 2000)
Aalto, Klaus ; Anttonen, Petri ; Brotherus, Elina ; Charpentier, Päivi ; Harada, Chikako ; Helorinne, Harri ; Hikk Group ; Hyötyläinen, Ilona ; Konttinen, Eeva ; Koskinen, Anne ; Kotwica, Petri ; Kupiainen, Lotta ; Lankinen, Katriina ; Leppänen, Kirsti ; Lerviks, Marcus ; Liusvaara, Outi ; Luukkonen, Ismo ; Mäkelä, Juha ; Matikainen, Tiia ; Nenonen, Juha ; Oksa, Rimma ; Päivinen, Sirpa ; Project Design Team ; Puolakka, Panu ; Rissanen, Mirjami ; Ruoho, Heikki ; Salmenperä, Aleksi ; Simolin, Kristian ; Simonsson, Kim ; Sorvali, Sami ; Suhonen, Paola ; Umeda, Hiroki ; Vesmanen, Esa ; von Weissenberg, Janina ; Zia
Engels & Fins
Think, UIAH (University of Art and Design Helsinki), 18.5. - 14.7.2000
boek